Growth and Vascular Remodeling Factors during a Basketball Season in Adolescent Boys - Elias Armenis; Anastassios Philippou; Maria Maridaki; Panayiotis Baltopoulos; Maria Tsironi (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Background: Circulating factors during exercise training are implicated in the adaptive mechanisms of physical conditioning. However, there is lack of information regarding the effect of basketball training on circulating growth and vascular remodeling factors in adolescents. The purpose of this study was to characterize the serum insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), matrix metalloproteinase 3 (MMP-3), albumin (ALB) and aldolase (ALD) responses in healthy adolescent boys over the course of a regular basketball season, and compared them with age- and sex-matched participants not involved systematically in any physical activity. Materials and methods: We evaluated systemic and body composition changes in basketball athletes (n=34; mean age 17.1±0.7 yrs) and controls (n=21; mean age 17.2±0.9 yrs) before training, at peak season (8 wks), and at the end of the season (32 wks). Results: Changes in % body fat and body mass index (BMI) were observed in the training group (TG) over time (P<0.05-0.001), while these parameters remained unchanged in the control group (CG). TG exhibited higher serum ALB and ALD levels compared with CG (P<0.001) while they did not change over time (P>0.05). Circulating IGF-1, VEGF and MMP-3 levels increased in TG over time (P<0.01) and were higher compared to CG (P<0.001), in which there were not any changes.